Gender Differences in Associated and Predictive Factors of Anxiety and Depression in People With Epilepsy - Liu, Zhao; Yin, Rong; Fan, Ze; Fan, Hong; Wu, Haiyan; Shen, Baorui; Wu, Shengxi; Kuang, Fang (Frontiers in Psychiatry, 2020)
Purpose: Comorbid anxiety and depressive disorders in people with epilepsy (PWE) are highly prevalent and associated with low quality of life (QOL) and may even lead to poor outcomes of epilepsy. Among the various factors that affect these negative emotional comorbidities, possible gender differences remain poorly understood and are often neglected. This research aimed to determine whether there are discrepancies in the prevalence and moderating factors of anxiety and depression between men and women with epilepsy in a hospital in northwest China.Methods: A total of 158 adult PWE (female: N=65; 41.1%) completed self-report questionnaires, including the Self-rating Anxiety Scale (SAS), the Self-rating Depression Scale (SDS), the Chinese version of the Quality of Life in Epilepsy-31 (QOLIE-31) inventory and the Pittsburgh Sleep Quality Inventory (PSQI). The comparison between male and female PWE was made by regression analysis.Results: For the prevalence of anxiety and depression in PWE, no gender difference was found in this study. However, the moderating factors of psychiatric comorbidities were significantly different between men and women: male PWE with comorbid anxiety were more likely to be affected by sleep quality, while anxiety symptoms in female PWE were closely associated with the frequency of seizures. Education years and QOL social function were significant indicators of depression in male PWE but not in female PWE. The important and common predictor for anxiety and depressive symptoms in PWE was QOL Energy/Fatigue, with male patients being more affected.Conclusion: For the PWE included in this study, the prevalence of comorbid anxiety and depressive disorders in PWE was similar for men and women, but the moderating factors affecting comorbid anxiety and depressive disorders differed between genders: male PWE were more likely to be affected by psychosocial factors, while female PWE were more influenced by epilepsy itself. This exploration suggests that gender-specific health care should be considered in epilepsy therapy to improve the psychiatric condition and QOL of PWE, and different treatments should be conducted for male and female PWE to prevent negative emotional comorbidities.